2005
DOI: 10.1155/2005/514813
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coinfection with Hepatitis B and Hepatitis C Viruses

Abstract: Acute coinfection of hepatitis B virus (HBV) and hepatitis C virus (HCV) is rare. The few previously reported cases all describe acute HBV followed by acute HCV, leading to HBV clearance but chronic HCV. This is the first reported case of acute concurrent infection and spontaneous clearance of both HBV and HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…HCV superinfection is more frequent, while HBV superinfection is rare [ 7 - 8 ]. In addition, acute HBV/HCV coinfection is more prevalent in PWID [ 9 ]. Most HBV/HCV-coinfected patients have HCV RNA levels similar to those in patients with HCV mono-infection, but relatively lower levels of serum HBV DNA compared to patients with chronic HBV mono-infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…HCV superinfection is more frequent, while HBV superinfection is rare [ 7 - 8 ]. In addition, acute HBV/HCV coinfection is more prevalent in PWID [ 9 ]. Most HBV/HCV-coinfected patients have HCV RNA levels similar to those in patients with HCV mono-infection, but relatively lower levels of serum HBV DNA compared to patients with chronic HBV mono-infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to an Italian investigation that showed active HBV-HCV indicators in 30 patients with HCV infection, the chronicity rates were equivalent to individuals with a single infection with either of the viruses. Biphasic alanine aminotransferase elevation was also observed in the case of HBV-HCV coinfection ( Yan and Lee, 2005 ). Several reports have documented that de novo HCV superinfection in the setting of chronic HBV infection can result in HBeAg seroconversion and clearance of HBsAg.…”
Section: Diagnosis Of Coinfectionmentioning
confidence: 99%
“…While the long-term outcome of co-infection or superinfection with different hepatotropic viruses responsible for chronic liver disease like HBV, HDV and HCV is expected to be poor [3,[7][8][9]12], the short-term evolution of these infrequent conditions is still largely unknown, especially when these infection are diagnosed in their acute phase [5,13], like in our patient. Chen et al reported HCV chronicization among subjects diagnosed with a concomitant HBV-HCV co-infection [13], while Yan and Lee described the first case of spontaneous clearance of both HBV and HCV after an acute co-infection [14]. On the other hand, an already advanced HCV hepatitis had its virus cleared without a specific therapy also during HIV infection [15].…”
Section: Discussionmentioning
confidence: 99%